The laws of medicine : field notes from an uncertain science - Mukherjee, Siddhartha, ....- (New York : TED Books / Simon & Schuster, 2015)
Essential, required reading for doctors and patients alike: A Pulitzer Prize-winning author and one of the world's premiere cancer researchers reveals an urgent philosophy on the little-known principles that govern medicine - and how understanding these principles can empower us all.